2024
DOI: 10.3390/ijms25052516
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Insulin-Regulated Aminopeptidase by Imidazo [1,5-α]pyridines—Synthesis and Evaluation

Karin Engen,
Thomas Lundbäck,
Anubha Yadav
et al.

Abstract: Inhibition of insulin-regulated aminopeptidase (IRAP) has been shown to improve cognitive functions in several animal models. Recently, we performed a screening campaign of approximately 10,000 compounds, identifying novel small-molecule-based compounds acting as inhibitors of the enzymatic activity of IRAP. Here we report on the chemical synthesis, structure-activity relationships (SAR) and initial characterization of physicochemical properties of a series of 48 imidazo [1,5-α]pyridine-based inhibitors, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…More recently, our group screened a library of 10,500 small molecules and identified various lead compounds [44], including arylsulfonamides [45], that enhance dendritic spine density in primary hippocampal neuron cultures [46], and un-competitive IRAP inhibitors encompassing a spiro-oxindole dihydroquinazolinone scaffold [47] and an imidazo [1,5α]pyridine scaffold [48]. Additional selective inhibitor leads targeting an allosteric site in IRAP were identified after applying a virtual docking approach [49], and it was reported that modulators of the structurally related hERAP2 have also been identified from a highthroughput screen (HTS) [50].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, our group screened a library of 10,500 small molecules and identified various lead compounds [44], including arylsulfonamides [45], that enhance dendritic spine density in primary hippocampal neuron cultures [46], and un-competitive IRAP inhibitors encompassing a spiro-oxindole dihydroquinazolinone scaffold [47] and an imidazo [1,5α]pyridine scaffold [48]. Additional selective inhibitor leads targeting an allosteric site in IRAP were identified after applying a virtual docking approach [49], and it was reported that modulators of the structurally related hERAP2 have also been identified from a highthroughput screen (HTS) [50].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several efforts have been initiated to develop pharmacologically useful inhibitors of IRAP's aminopeptidase activity, in particular in the areas of cognition 7,8 and fibrosis 9,10 . IRAP inhibitors have been developed either by rational substrate-inspired design or after random chemical or virtual library screening and include pseudophosphinic peptide transition-state-analogues, aryl sulfonamides, benzopyran derivatives, diaminobenzoic acid derivatives, imidazopyridines and cyclic peptide analogues [11][12][13] . Several of these compounds have been shown to be active in cellular and in in vivo systems relating to IRAP biological activities, such as promoting the formation of functional dendritic spines in primary hippocampal neuron cultures 14 , regulation of acetylcholine-mediated vasoconstriction 15 and glucose tolerance in insulin-resistant Zucker fatty rats 16 .…”
Section: Introductionmentioning
confidence: 99%